Effect of Liquefaction Induced Lateral Spreading on Seismic Performance of Pile Foundations - G. M. Basavana Gowda; S. V. Dinesh; L. Govindaraju; R. Ramesh Babu (Civil Engineering Journal, 2021)
Seismically active areas are vulnerable to liquefaction, and the influence of liquefaction on pile foundations is very severe. Study of pile-supported buildings in liquefiable soils requires consideration of soil-pile interaction and evaluation of the interaction resulting from movement of soil surrounding the pile. This paper presents the results of three-dimensional finite difference analyses conducted to understand the effect of liquefiable soils on the seismic performance of piles and pile groups embedded in stratified soil deposits using the numerical tool FLAC3D. A comparative study has been conducted on the performance of pile foundations on level ground and sloping ground. The soil model consists of a non-liquefiable, slightly cemented sand layer at the top and bottom and a liquefiable Nevada sand layer in between. This stratified ground is subjected to 1940 El Centro, 2001 Bhuj (India) earthquake ground motions, and harmonic motion of 0.3g acceleration. Parametric studies have been carried out by changing the ground slope from 0° to 10° to understand the effects of sloping ground on pile group response. The results indicate that the maximum bending moments occur at boundaries between liquefiable and non-liquefiable layers, and that the bending moment increases with an increase in slope angle. The presence of a pile cap prevents horizontal ground displacements at ground level. Further, it is also observed that the displacements of pile groups under sloping ground are in excess of those on level ground due to lateral spreading. Doi: 10.28991/CEJ-SP2021-07-05 Full Text: PDF